Disinfection using ultraviolet radiation. Methods for quantitative testing of automated ultraviolet disinfection activities by direct illumination. Determination of bactericidal, mycobactericidal, sporicidal, yeasticidal, fungicidal, virucidal and phagocidal activities. (31st March 2022) - British Standards Institution,
No abstract available